Supplementation With Spirulina Reduces Infarct Size and Ameliorates Cardiac Function in a Pig Model of STEMI - Vilahur, Gemma; Sutelman, Pablo; Ben-Aicha, Soumaya; Mendieta, Guiomar; Radiké, Monika; Schoch, Leonie; Casaní, Laura; Borrell-Pagés, María; Padro, Teresa; Badimon, Lina (Frontiers in Pharmacology, 2022)
Background and Aims: Myocardial infarction (MI) is the clinical manifestation of atherosclerotic coronary artery disease. Spirulina is an algae known to ameliorate cardiometabolic disorders and with proven anti-inflammatory and anti-oxidant effects. We investigated, in a highly translatable animal model, whether oral supplementation with spirulina protects against the deleterious effects triggered by ST-elevation MI (STEMI). Methods: Pigs were fed a regular diet supplemented with spirulina (1 gr/animal/bid) or placebo-control for 10days. Thereafter, animals were subjected to 1.5h percutaneous balloon-induced coronary occlusion (STEMI) followed by 2.5h reperfusion and then sacrificed. We assessed infarct size and cardiac function. Blood samples and infarcted and remote myocardial tissue were obtained. Results: Spirulina supplementation reduced infarct size by 64%, increased myocardial salvage index by 18%, and improved cardiac function by 30% vs. controls (p<0.05). These benefits were associated with attenuation in DNA-oxidative damage and apoptotic markers in the infarcted myocardium, and higher AMPK activation and lower MCP-1 in the entire heart. Systemically, spirulina attenuated Cox-2 expression in STEMI-activated peripheral blood mononuclear cells and enhanced TNF-α release acutely post-STEMI. Additionally, spirulina decreased weight gain progression over time (p<0.05) without changes in lipids, glucose, liver or kidney parameters. Conclusion: A 10-day supplementation with spirulina exerts cardioprotection in a preclinical setting of STEMI by limiting cardiac damage and improving ventricular contractility through anti-oxidative, anti-inflammatory, and anti-apoptotic mechanisms.